Pengaruh Internal Locus Of Control Terhadap Perilaku Prososial Pada Siswa SMAN 1 Menganti-Gresik - Larasati A Nandira; Muhimmatul Hasanah; Setyani Alfinuha (Universitas Muhammadiyah Gresik, 2023)
This study aims to empirically examine the effect of internal locus of control on prosocial behavior in students at SMA Negeri 1 Menganti – Gresik. This study analyzes the data obtained from a sample of 267 people. The measuring scale used is the Sala Internal Locus of Control and the Prosocial Behavior Scale. The statistical analysis method used is simple linear regression analysis. The results show that significance (p) = 0.000 less than 0.05 which means that the internal locus of control has a significant influence on prosocial behavior in students at SMA Negeri 1 Menganti – Gresik with internal influence locus of control on prosocial behavior of 23.1%. The results of the categorization of this study indicate that the subject has a moderate category on prosocial behavior and a moderate category on internal locus of control.